Targeting the kynurenine pathway: another therapeutic opportunity in the metabolic crosstalk between cancer and immune cells - Kang, Irene; Theodoropoulos, George; Wangpaichitr, Medhi (Frontiers in Oncology, 2025)
The pivotal role of metabolic reprogramming in cancer-related drug resistance, through the tryptophan-catabolized kynurenine pathway (KP), has been particularly underscored in recent research. This pathway, driven by indoleamine 2,3-dioxygenase 1 (IDO1), facilitates immune evasion and promotes tumor progression by fostering an immunosuppressive environment. In Phase III investigation of the combination of IDO1 inhibition with immune checkpoint inhibitors (ICIs), the combination therapy was not efficacious. In this review, we revisit current advances, explore future directions, and emphasize the importance of dual inhibition of the KP rate-limiting enzymes IDO1 and tryptophan 2,3-dioxygenase-2 (TDO2) in appropriate patient populations. We propose that dual inhibition may maximize the therapeutic potential of KP inhibition. Additionally, we delve into the complex cellular interactions in cancer and metabolic dependencies within the tumor microenvironment (TME). Insights from preclinical studies, recent clinical trials, and promising therapeutic combinations will be discussed to elucidate and promote a clear path forward for the direction of KP research into cancer-related outcomes.